2011
DOI: 10.1111/j.1439-0272.2010.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiologically assessed testicular changes in infertile males with varicocele

Abstract: The aim of this study was to assess vascular disturbances in the testis of infertile males associated with varicocele. In total, 124 consecutive male subjects were divided into the following groups: healthy fertile controls (n = 10), Gp1 (n = 28); infertile males with subclinical varicocele, Gp2 (n = 26); infertile males with grade I left varicocele, Gp3 (n = 28); infertile males with grade II left varicocele and Gp4 (n = 32); infertile males with grade III left varicocele. They were subjected to colour duplex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…If venous pressure alone increases as in varicocele, a reflex increase in precapillary resistance with diminished testicular blood flow com- promises the nutrient supply to the testis [16]. It is concluded that there are decreases in testis size, testicular perfusion, blood velocity, and testicular arteries diameter in infertile males associated with varicocele [14]. Actually, testicular scintigraphy has more scientific value than the practical one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If venous pressure alone increases as in varicocele, a reflex increase in precapillary resistance with diminished testicular blood flow com- promises the nutrient supply to the testis [16]. It is concluded that there are decreases in testis size, testicular perfusion, blood velocity, and testicular arteries diameter in infertile males associated with varicocele [14]. Actually, testicular scintigraphy has more scientific value than the practical one.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Hassan, scintigraphic measures showed significantly decreased arterial perfusions at early 15 s in testicular arterial blood velocity [14]. Suga et al [15] reported decreased arterial perfusion of leftsided varicocele after sequential scrotal scintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Varicocele is the most common preventable cause of male infertility. 6 The most common findings following semen analysis are decreased motility and sperm density, and increased number of pathologic sperm forms in adults. 5 Radiological and histological testicular changes may be seen in patients with varicocele.…”
Section: Commentsmentioning
confidence: 99%
“…Hassan et al sugieren que la velocidad de la sangre arterial, los diámetros arteriales testiculares y la perfusión testicular disminuyeron significativamente en pacientes con varicocele de alto grado en comparación con los controles sanos 6 . Los hallazgos más comunes después del análisis de semen son el descenso de la motilidad y la densidad de los espermatozoides y el aumento del número de formas patológicas de esperma en los adultos 7 .…”
Section: Comentariosunclassified